COMPETENCE-BASED APPROACH IN PROFESSIONAL EDUCATION: PROBLEMS AND PROSPECTS OF IMPLEMENTING INNOVATIVE METHODS USING INFORMATION TECHNOLOGIES (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article discusses the problems and prospects of introducing a competence-based approach and innovative methods using information technology in vocational education.